2021
DOI: 10.31129/lumat.9.1.1414
|View full text |Cite
|
Sign up to set email alerts
|

Co-designing cross-setting activities in a large-scale STEM partnership program – Teachers’ and students’ experiences

Abstract: STEM partnerships are popular initiatives but can be challenging to implement in practice. Accordingly, within the context of a nationwide, cross-setting STEM partnership program in Norway – Lektor2 – a co-design tool was introduced to support teachers to collaborate with STEM professionals in developing curriculum units involving authentic STEM problems and practices. Thus, the purpose of this study was to describe the teachers’ and students’ experiences from the curriculum units based on the co-design tool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The context was realistic -the transport company's transition to renewable transport technologies, but the commission -or the problem -was a fictive situation: the transport company did not really need the students' help. This aligns with our earlier study involving a much higher number of participants (Kostøl et al, 2021), in which we argue that the extent to which the commission is genuine -and not fictive -is important for the students' motivation and engagement in context-based curriculum units within Lektor2. Despite the slight difference in the authenticity between the context and commission, the category comparing with normal teaching (comprising of the codes context-based curriculum as a different approach and student outcomes from curriculum unit), reveals that both the teachers and students reported an increased effort among the students compared to normal teaching, and that the students were better at thinking and reflecting.…”
Section: Discrepancy Between Context and Commissionsupporting
confidence: 91%
See 3 more Smart Citations
“…The context was realistic -the transport company's transition to renewable transport technologies, but the commission -or the problem -was a fictive situation: the transport company did not really need the students' help. This aligns with our earlier study involving a much higher number of participants (Kostøl et al, 2021), in which we argue that the extent to which the commission is genuine -and not fictive -is important for the students' motivation and engagement in context-based curriculum units within Lektor2. Despite the slight difference in the authenticity between the context and commission, the category comparing with normal teaching (comprising of the codes context-based curriculum as a different approach and student outcomes from curriculum unit), reveals that both the teachers and students reported an increased effort among the students compared to normal teaching, and that the students were better at thinking and reflecting.…”
Section: Discrepancy Between Context and Commissionsupporting
confidence: 91%
“…Current research concludes that context-based approaches can have a positive influence on students' attitudes to science and that students learn the same amount of science in context-based teaching as in traditional science teaching (Bennett, 2016;Bennett et al, 2007). Studies have shown that context-based curriculums involving collaboration with external STEM professionals also inform students about the relevance of science outside school and possible careers (Houseal et al, 2014;Kostøl et al, 2021;Parker et al, 2020;Tsybulsky, 2019). However, studies have also identified challenges with context-based science education.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations